2004
DOI: 10.1074/jbc.m401023200
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Adenosine Deaminase Binds and Stimulates Plasminogen Activation on 1-LN Human Prostate Cancer Cells

Abstract: Adenosine deaminase (ADA) is expressed intracellularly by all cells, but in some tissues, it is also associated with the cell surface multifunctional glycoprotein CD26/ dipeptidyl peptidase IV. By modulating extracellular adenosine, this "ecto-ADA" may regulate adenosine receptor signaling implicated in various cellular functions. CD26 is expressed on the surface of human prostate cancer 1-LN cells acting as a receptor for plasminogen (Pg). Since ADA and Pg bind to CD26 at distinct but nearby sites, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…This is in agreement with the affinity constants of ADA to bind to these two proteins. It has been reported that the affinity of 125 I-ADA by CD26 is around 18 nM ( Gonzalez-Gronow et al, 2004 ) (equivalent to 0.7 μg/ml), and its affinity by A 1 R is around 230 nM ( Saura et al, 1996 ) (equivalent to 9 μg/ml). These values indicate that first ADA binds to CD26 and then to AR, so that a balance of ADA concentrations occurs between the bars of 0.1 and 10 μg/ml in Figure 4A to form a trimeric complex, where ADA has enough concentration to bridge CD26 and AR, but higher concentrations shift the equilibrium toward dimeric ADA-CD26 and ADA-AR complexes.…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with the affinity constants of ADA to bind to these two proteins. It has been reported that the affinity of 125 I-ADA by CD26 is around 18 nM ( Gonzalez-Gronow et al, 2004 ) (equivalent to 0.7 μg/ml), and its affinity by A 1 R is around 230 nM ( Saura et al, 1996 ) (equivalent to 9 μg/ml). These values indicate that first ADA binds to CD26 and then to AR, so that a balance of ADA concentrations occurs between the bars of 0.1 and 10 μg/ml in Figure 4A to form a trimeric complex, where ADA has enough concentration to bridge CD26 and AR, but higher concentrations shift the equilibrium toward dimeric ADA-CD26 and ADA-AR complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Pg binds via its 2,3-linked sialic acid residues attached to Thr 345 O-linked carbohydrate chains to CD26 [12]. Pg also binds via its kringle 4 to adenosine deaminase in complex with CD26 [13]. Both these interactions with CD26 result in an augmented Pm generation which, in addition to facilitating cell invasion, may also stimulate generation of angiostatin directly on the cell surface.…”
Section: Introductionmentioning
confidence: 94%
“…That this artifact was due to contaminating dA deaminase activity was confirmed by the absence of dI formation when coformycin, a specific inhibitor of dA/A deaminase, was added during DNA processing steps (14). The presence of dA deaminase activity is not surprising given the role of adenine deaminase in purine metabolism, the adenosine deaminase (ADA) associated with cell surface glycoproteins to regulate adenosine receptor signaling (46), and the adenosine deaminases termed ADARs that mediate RNA editing (47)(48)(49)(50). Among the known ADARs, ADAR1 was found to recognize Z-DNA when flanked by B-DNA (51).…”
Section: Adventitious Nucleobase Deaminationmentioning
confidence: 99%